Contribution to O’Donnell et al. (2017, in press). Registered replication report: Dijksterhuis & van Knippenberg (1998). - Philipp MC; Williams MN; Cannon PC; Drummond A (Association for Psychological Science, 2018)
Dijksterhuis and van Knippenberg (1998) reported that participants primed with a category associated with intelligence (“professor”) subsequently performed 13% better on a trivia test than participants primed with a category associated with a lack of intelligence (“soccer hooligans”). In two unpublished replications of this study designed to verify the appropriate testing procedures, Dijksterhuis, van Knippenberg, and Holland observed a smaller difference between conditions (2%–3%) as well as a gender difference: Men showed the effect (9.3% and 7.6%), but women did not (0.3% and −0.3%). The procedure used in those replications served as the basis for this multilab Registered Replication Report. A total of 40 laboratories collected data for this project, and 23 of these laboratories met all inclusion criteria. Here we report the meta-analytic results for those 23 direct replications (total N = 4,493), which tested whether performance on a 30-item general-knowledge trivia task differed between these two priming conditions (results of supplementary analyses of the data from all 40 labs, N = 6,454, are also reported). We observed no overall difference in trivia performance between participants primed with the “professor” category and those primed with the “hooligan” category (0.14%) and no moderation by gender.
Keywords: priming; replication; intelligence; 1701 Psychology; 1702 Cognitive Sciences